2015
DOI: 10.1016/j.leukres.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Final results of EFC6663: A multicenter, international, phase 2 study of alvocidib for patients with fludarabine-refractory chronic lymphocytic leukemia

Abstract: Purpose Chronic lymphocytic leukemia (CLL) patients refractory to fludarabine based therapies have poor outcomes with currently available therapies. Early phase studies of alvocidib showed activity in relapsed CLL including patients with high risk genomic features and those refractory to fludarabine. A multi-center, international, phase II study of alvocidib in fludarabine refractory CLL was undertaken to validate these early results. Patients and Methods Patients with fludarabine refractory CLL or prolympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…The drug concentrations tested in our validation studies were in the range of clinically achievable concentrations for each of the KIs, with achievable plasma concentrations of 0.25 mM, 0.5 mM, and up to 1.1 mM reported for sunitinib, [56][57][58][59][60] ibrutinib (NCT01105247), 66 and idelalisib (NCT00710528, NCT01090414), 48 respectively. P16 P17 P18 P19 P20 P21 P22 P23 P24 P25 P26 P27 P16 P17 P18 P19 P20 P21 P22 P23 P24 P25 P26 P27 P16 P17 P18 P19 P20 P21 P22 P23 P24 P25 P26 P27 sunitinib Other KIs such as dasatinib [67][68][69][70][71] and flavoperidol [72][73][74] were identified as having a high total kill with venetoclax ( Figure 3A, arrow and arrowhead, respectively). In combination with venetoclax in vitro, dasatinib ranked in position 10 of 31 licensed drugs and its venetoclax-enhanced effect was intermediate and detected in only 5 of 13 patients ( Figure 3A-B, arrow).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug concentrations tested in our validation studies were in the range of clinically achievable concentrations for each of the KIs, with achievable plasma concentrations of 0.25 mM, 0.5 mM, and up to 1.1 mM reported for sunitinib, [56][57][58][59][60] ibrutinib (NCT01105247), 66 and idelalisib (NCT00710528, NCT01090414), 48 respectively. P16 P17 P18 P19 P20 P21 P22 P23 P24 P25 P26 P27 P16 P17 P18 P19 P20 P21 P22 P23 P24 P25 P26 P27 P16 P17 P18 P19 P20 P21 P22 P23 P24 P25 P26 P27 sunitinib Other KIs such as dasatinib [67][68][69][70][71] and flavoperidol [72][73][74] were identified as having a high total kill with venetoclax ( Figure 3A, arrow and arrowhead, respectively). In combination with venetoclax in vitro, dasatinib ranked in position 10 of 31 licensed drugs and its venetoclax-enhanced effect was intermediate and detected in only 5 of 13 patients ( Figure 3A-B, arrow).…”
Section: Discussionmentioning
confidence: 99%
“…Alvocidib had high clinical activity in patients with advanced fludarabinerefractory CLL; however, acute tumor lysis syndrome limited its use clinically. 74 Given that tumor lysis syndrome is associated with both alvocidib and venetoclax, 9,74 combining the 2 agents might be too toxic. DMSO venetoclax P34 P35 P36 P37 P38 P39 P34 P35 P36 P37 P38 P39 P34 P35 P36 P37 P38 P39 sunitinib A1210477 Unstimulated 2S stimulated navitoclax P34 P35 P36 P37 P38 P39 P34 P35 P36 P37 P38 P39 P34 P35 P36 P37 P38 P39 sunitinib A1210477 Our results suggest that a personalized drug selection based on screening may identify clinically relevant drugs that can overcome resistance to venetoclax by altering microenvironmental signaling pathways (Figure 7Biii).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Despite these advances, 5-year overall survival (OS) remains dismal (;20%) among adults age $60 years treated at academic centers and on multiinstitutional clinical trials by using established first-line regimens. 5,6 European population-based analyses have similarly revealed suboptimal outcomes in this population. [7][8][9][10] Emerging novel agents provide substantial antileukemic effect with manageable toxicity and may represent attractive therapeutic strategies for older patients with ALL, either as components of initial therapy or as treatment at relapse.…”
Section: Org Frommentioning
confidence: 95%
“…3 The pan-CDK inhibitor flavopiridol demonstrated clinical efficacy 4,5 but was associated with tumor lysis syndrome (TLS), which occurred in 25% of patients, some of whom required hemodialysis. 6 Dinaciclib is a novel, potent, small-molecule CDK inhibitor that selectively inhibits CDK1, 2, 5, and 9 at 50% inhibitory concentration values in the 1-to 4-nM range. 7,8 In in vitro studies, dinaciclib induced apoptosis and/or cell growth arrest in various solid and hematopoietic tumor cell models.…”
mentioning
confidence: 99%
“…Although flavopiridol exhibited significant anti-tumour activity in preclinical studies 111 , clinical phase II studies reported insufficient efficacy for solid cancers. However, some evidence for clinical activity was observed in haematological malignancies (TABLE 2) 113, 114 .…”
Section: Targeting Cdks In Cancer Therapymentioning
confidence: 99%